Effect of Hydroalcoholic Extract of Dodoneae viscosa on Pain and Anxiety in Male Rats - Narges Behzadi Rad; Zohreh Valizadeh; Maryam Rafeei Rad (Institue of Medicinal Plants, ACECR, 2018)
Background: Pain is caused by acute or potential tissue damage. Anxiety disorders are common psychiatric disorders in humans that are experienced in threatening situations. Herbal drugs have fewer side effects than chemical drugs. Objective: Evoulution of Hydroalcoholic Extract of Dodoneae viscosa on Pain and Anxiety in Male Rats. Methods: in this study 35 Wister male rats randomly divided in to 5 groups: 1) control group, 2) sham group that received normal saline, 3-5) groups received 100,200,400 mg/kg extract for 10 days by gavages respectively. Pain was tested by formalin test. Anxiety was tested by open filed. Results Dotoneae viscosa extract had a dose-dependent anti-nociceptive effect on chronic pains caused by the formalin injection (P<0.001). Also check anti-anxiety effects in open box test indicated significant difference in dose of 100, 200 mg/kg extract (effective dose) in Number of passages from the central lines (P<0.001),(P<0.01), Time spend in central line (P<0.001), starch (P<0.001), Grooming (P<0.01), (P<0.05). 400mg/kg had no effect. Results: According to the presented data, the concentration and amount of silymarin in different extracts was compared. The extract obtained from ground seeds with methanol was able to reach the most amount of silymarin while the highest concentration of silymarin was obtained from the extract of ground pericarp with ethanol 80%. Conclusion: The results indicated that Dodoneae viscosa extract as an antioxidant and anti-inflammatory agent is effective in the treatment of inflammatory diseases and relieving long-term pain such as opioid drugs.